2018
DOI: 10.1177/1724600818760234
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of PIVKA-II in hepatocellular carcinoma patients receiving curative ablation: A systematic review and meta-analysis

Abstract: This meta-analysis suggests that elevated PIVKA-II is a predictor of unfavorable overall survival and recurrence-free survival in hepatocellular carcinoma patients receiving curative ablation. More rigorous studies are warranted to confirm the clinical utility of PIVKA-II in determining hepatocellular carcinoma prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…and between AFP and PIVKA-II. It is known that a high value of AFP or PIVKA-II is a poor prognosis marker of HCC (30,31). Our study showed that high levels of FL-GPC3 were strongly related to HCC recurrence, and this might also reflect poor prognosis.…”
Section: Discussionsupporting
confidence: 48%
“…and between AFP and PIVKA-II. It is known that a high value of AFP or PIVKA-II is a poor prognosis marker of HCC (30,31). Our study showed that high levels of FL-GPC3 were strongly related to HCC recurrence, and this might also reflect poor prognosis.…”
Section: Discussionsupporting
confidence: 48%
“…Regarding the role of PIVKA-II as treatment response marker, a recent meta-analysis showed that increased PIVKA-II levels could predict worsening overall survival and recurrence-free survival in patients with HCC who had curative ablation [48] . More studies are needed to confirm the clinical utility of PIVKA-II for HCC prognosis.…”
Section: Dcpmentioning
confidence: 99%
“…For instance, Kim et al, reported that elevated serum PIVKA-II level was associated with microvascular invasion in small HCC (< 2 cm), and serum PIVKA-II level ≥ 200 mAU/mL was a predisposing factor for tumor recurrence after surgery [22]. Another recent meta-analysis study revealed that higher PIVKA-II could be a predictor of unfavorable overall survival in hepatocellular carcinoma patients receiving curative ablation [23]. Moreover, PIVKA-II has been employed as an important factor in consideration of liver transplantation for HCC patients [24].…”
Section: Discussionmentioning
confidence: 99%